Development and evaluation of mixture formulations to enhance concrete resistance to microbial-induced corrosion - Roz-Ud-Din Nassar; Parviz Soroushian; Tewodros Ghebrab; Muhammad Sufyan-Ud-Din (Results in Materials)
Diverse strategies were designed and evaluated for enhancement of concrete resistance to microbial-induced corrosion through refinement of concrete chemistry, pore structure, transport attributes, and amenability to microbial growth. Laboratory and insitu field experiments were implemented in order to screen different strategies. The study considered strategies involving; the use of hydrophobic additives for rendering capillary pores water-repelling; blend of pozzolans to refine the chemistry and pore system characteristics of concrete; use of polymer emulsions for refinement of concrete porosity, affinity for moisture and amenability to microbial growth; use of anti-microbial constituent for reducing the amenability of concrete to microbial growth; and incorporation of polyvinyl alcohol fibers for enhancing mechanical performance of concrete mixtures, were investigated.Test results indicate that two admixture formulations comprising of hydrophobic additive, and blend of pozzolan offer the best promise to achieve substantially enhanced resistance to microbial-induced corrosion and acid resistance in the aggressive sewer environment.